A staggered multiphysics framework for salt crystallization-induced damage in porous building materials. (18th October 2021) - Castellazzi, G.; D'Altri, A.M.; de Miranda, S.; Emami, H.; Molari, L.; Ubertini, F.
Abstract: In this paper, a staggered multiphysics framework is proposed for the numerical simulation of salt crystallization-induced damage in porous building materials, such as masonry. This staggered framework is based upon a multiphase model to account for salt transport and crystallization within the porous material and a plastic-damage model to account for the nonlinear mechanical behavior of the material. The staggered structure is composed of a two-way data exchange between the multiphase and the mechanical models. Firstly, crystallization pressure information is passed to the mechanical model to analyze the mechanical response of the material. Secondly, the mechanical outcomes (e.g. damage distribution) are used to update some multiphase model properties (e.g. tortuosity) allowing simulations also beyond the onset of damage. Few simple geometry-based relationships are discussed to update multiphase model properties along with damage. Numerical examples are used to show the capability of the proposed staggered framework for simulating complex interactions among salt transport, salt crystallization, and damage within the porous material, highlighting the possibilities of this modeling approach to conduct simulations also beyond the onset of damage. Highlights: A staggered multiphysics framework is proposed to analyze porous building materials The solution is based on a two-way data exchange between multiphase and mechanical models Salt crystallization-induced damage in masonry is numerically evaluated The multiphysics approach allows for the simulation also beyond the onset of damage